2022
DOI: 10.1016/j.jempfin.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of the limit order book on price dynamics

Abstract: We analyze whether the information in different parts of the limit order book affect prices differently. We distinguish between slopes of lower and higher levels of the bid and ask sides and include these four slope measures as well as midquote return and trade direction in a vector autoregressive model. Slope measures of the same side based on different levels affect both short-and long-run price dynamics quite differently, in line with the predictions based on recent theoretical models such as Foucault, Kada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Cenesizoglu, Dionne, and Zhou [58], and Hasbrouck and Saar [130]) demonstrated that traders might strategically choose to place their orders in different levels of the book depending on various factors, therefore limit orders at different price levels may contain different information content with respect to predicting future returns. A further study with more focus on the impact of multi-level OFIs over different time horizons is suggested.…”
Section: Discussion About Predictive Cross-impactmentioning
confidence: 99%
“…Cenesizoglu, Dionne, and Zhou [58], and Hasbrouck and Saar [130]) demonstrated that traders might strategically choose to place their orders in different levels of the book depending on various factors, therefore limit orders at different price levels may contain different information content with respect to predicting future returns. A further study with more focus on the impact of multi-level OFIs over different time horizons is suggested.…”
Section: Discussion About Predictive Cross-impactmentioning
confidence: 99%
“…A review of different NN applications in finance is provided in McNelis (2005), an early discussion on econometric applications can be found in Kuan and White (1994) and within time-series analysis in Hewamalage et al (2021), Qi andZhang (2008), andTeräsvirta et al (2005). Cenesizoglu et al (2022) analyzed the relationship between LOB variables and mid-price movements showing that it is possible to obtain economical gain from these variables and the mid-price return. Further, their causality analysis supports the use of lagged LOB variables for forecasting purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the statistical parametric models for stock price prediction, Cenesizoglu et al (2016) extracted the informative variables that characterize LOBs, so as to establish a vector auto-regressive (VAR) model to analyze how various features of the LOBs affect prices. Mondal et al (2014) evaluated the accuracy and variability of stock price forecasts using an auto-regressive integrated moving average (ARIMA) model.…”
Section: Introductionmentioning
confidence: 99%